MENGOPTIMALKAN PENGELOLAAN SARANA DAN PRASARANA KANTOR DI SMP SWASTA PENRAUJAN KEC. SUNGGAL KAB. DELI SERDANG - H. Tengku Darmansah; Audia Amanda Br Tarigan; Nur Aini; Zulfikar Lubis (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Management of office facilities and infrastructure is very important because it can affect employee performance at work, both in working time and comfort in doing work. With adequate office facilities and infrastructure, employee performance will increase so that they can work better and achieve optimal work results. Penraujan Private Middle School in Sunggal District, Deli Serdang Regency, which is one of the junior high schools in Sunggal Kanan, has adequate office facilities. Research on